Use of Back-Off Computation in Multilevel MPC - Arbiza, M.J. (2003)
The desired operating point in Model Predictive Control is determined by a local steadystate optimization, which may be based on an economic objective. In this paper we proposes the solution of a linear dynamic back-off problem to obtain a hierarchical scheme that ensures feasible operation in despite of disturbances. This is performed by computing the critical disturbances and expanding the optimization problem to ensure the existence of a control action that ensures the rejection of each perturbation.